Polymorphisms of genes encoding P2X7R, IL-1B, OPG and RANK in orthodontic-induced apical root resorption - Pereira, S. (2013)
ObjectiveOrthodontic-induced external apical root resorption (EARR) is a complex phenotype determined by poorly defined mechanical and patient intrinsic factors. The aim of this work was to construct a multifactorial integrative model, including clinical and genetic susceptibility factors, to analyze the risk of developing this common orthodontic complication. Materials and MethodsThis retrospective study included 195 orthodontic patients. Using a multiple-linear regression model, where the dependent variable was the maximum% of root resorption (%EARRmax) for each patient, we assessed the contribution of nine clinical variables and four polymorphisms of genes involved in bone and tooth root remodeling (rs1718119 from P2RX7, rs1143634 from IL1B, rs3102735 from TNFRSF11B, encoding OPG, and rs1805034 from TNFRSF11A, encoding RANK). ResultsClinical and genetic variables explained 30% of%EARRmax variability. The variables with the most significant unique contribution to the model were: gender (P<0.05), treatment duration (P<0.001), premolar extractions (P<0.01), Hyrax appliance (P<0.001) and GG genotype of rs1718119 from P2RX7 gene (P<0.01). Age, overjet, tongue thrust, skeletal class II and the other polymorphisms made minor contributions. ConclusionThis study highlights the P2RX7 gene as a possible factor of susceptibility to EARR. A more extensive genetic profile may improve this model.